Trophic Niche Partitioning of Freshwater Fish in Eutrophic Lakes: A Food Quality Perspective - Yiduo Luo; Fen Guo; Jing Lu; Xiaoguang Ouyang; Feilong Li; Wei Gao; Juan Tao; Yuan Zhang (Ecosystem Health and Sustainability)
Trophic niche analysis is essential for understanding species interactions and ecosystem functioning, especially in the context of environmental changes such as nutrient enrichment. While the effects of water nutrient enrichment on food webs have been widely studied, the role of long-chain polyunsaturated fatty acids (LC-PUFAs) in shaping fish trophic niches, particularly in eutrophic lakes, remains underexplored. This study investigated the impact of water nutrient enrichment on fish trophic niches by examining food resource quality, specifically LC-PUFAs, through field sampling and fatty acid composition analysis. Our results showed that water nutrient enrichment led to a reduction in LC-PUFA content in fish food sources, such as phytoplankton, periphyton, zooplankton, and invertebrates, causing a contraction of the fish trophic niche. Invasive fish species, such as Chanodichthys erythropterus, exhibited broader trophic niches and greater dietary flexibility compared to native fish species. The reduction in LC-PUFA content in these food sources emphasized the critical role of LC-PUFAs in sustaining fish trophic niche breadth. Fish species-specific physiological traits further influenced resource utilization, with generalist fish species showing greater adaptability to reduced food quality. These findings highlighted the crucial role of LC-PUFAs in maintaining fish trophic niches and underscored the importance of food resource quality in managing eutrophic ecosystems for biodiversity conservation and ecosystem stability.